RNAi: An innate gene knockdown mechanism - Srinivasan, Thangavelu; Sudarsanam, Dorairaj (Research in Biotechnology, 2011)
RNA interference (RNAi) is an evolutionary conserved mechanism in all eukaryotic cells whose role is to down-regulate the gene expression in the nucleus known as Transcriptional Gene silencing (TGS) and in the cytoplasm known as Post Transcriptional Gene Silencing (PTGS). It can occur at different stages of cell cycles during cell proliferation,Ã‚Â  developmental stage and cell death. An artificially induced Double Stranded RNA (dsRNA) in a eukaryotic organism like C. elegans can also cause RNAi by sequence specific gene silencing. The Double Stranded RNA (dsRNA) derived small RNAs (19-28nt in length) along with Argonaute protein, Dicer (RNase III like enzyme) and other cofactors act as molecular scissors which degrade the homologous mRNA. This effector-protein complex is termed as RNA-induced silencing complex (RISC) which searches for the homologous transcripts of mRNA to degrade them. The Small RNA which might be either a Small Interference RNA (siRNA) or a microRNA (miRNA) along with the effector complex directs the endonuclease cleavage to occur on the target mRNA thereby preventing the expression of transcripts. This overall process is termed as RNAi (RNA interference).